Interleukin-6 Expression and Stage, Location, And Degree Of Differentiation On Colorectal Cancer Patients - Muchizal Aqni; Fadhila Rianty (Nusantara Journal of Multidisciplinary Science, 2023)
Interleukin-6 (IL-6) is a type of inflammatory cytokine that mediates hematopoiesis and lymphocyte activation. Furthermore, recent studies showed that it has a role as a mediator of tumor progression. The expression of this cytokine correlated with tumor grade, poor survival, clinical stage of colorectal cancer, and metastasis. This allows IL-6 to be useful in diagnosis and predict the poor prognosis of colorectal cancer for treatment management to be carried out more aggressively. Also, Interleukin-6 is involved in colorectal cancer metastases because it is detected in the cell supernatants and serum of patients. However, it is not clear whether it is involved in the pathogenesis, formation, or metastasis of cancer. This study aimed to ascertain the expression of Interleukin-6 with a clinicopathological overview in colorectal cancer patients, specifically to determine its relationship with the stage, location, metastasis, and disease differentiation. This is an analytical observational study with a cross-sectional design to determine the relationship between Interleukin-6 expression and clinical features, stage, as well as degree of differentiation in colorectal cancer patients. Furthermore, this study was conducted in our institution from September 2019 to May 2020. 32 research subjects met the inclusion and exclusion criteria. Based on the analysis, it was shown that IL-6 expression has a significant relationship with the tumor stage (p=0.001) and differentiation (p=0,034). However, location do not show a significant relationship (p=0.098). IL-6 may be an important indicator for predicting the prognosis of colorectal cancer patients and could be a future therapeutic approach.